Situations, Problems, and Needs in Teaching English of Grades 1-6 Teachers in the Central Region of Thailand - Kanya Kongsoongnoen; Sasiwimon Sutthisan (International Journal of Pedagogy and Teacher Education, 2017)
The purpose of this research was to examine the situations, problems, and needs in teaching English of grades 1-6 teachers in five provinces located in the five provinces in the central region of Thailand: Lop Buri, Sing Buri, Saraburi, Suphan Buri, and Ang-Thong in 2016. A questionnaire comprising both open and closed-ended questions was sent to the English teachers in the area and 170 teachers responded back. Percentage, mean and standard deviation were applied to analyze quantitative data whereas content analysis was conducted for qualitative data. The results of the teachers’ questionnaire response indicated most participants had no degree in English, but had 1-5 year experience in teaching English. When considering on the teachers’ perceptions on teaching English using Likert Scales, their satisfaction was at a moderate level in every item (teaching situations, contents, learning activities, learning materials, and evaluation). Most teachers mentioned that lacking teaching methodologies, contents, and skills in English were of concern when teaching English, therefore, they had their students learn from the programs themselves and sometimes the teachers used the text books to teach. The findings also showed that the teachers needed teaching English training especially the English teaching methodologies. Lacking qualified teachers to teach English in primary grades was critical particularly with Grades 1-2.Except where otherwise noted, content on this site is licensed under a Creative Commons Attribution 4.0 International License